A Dynamic Model For Poultry Supply Chain In West Java - Rahmat Ridlo Aminuddin; Liane Okdinawati (Profesional Muda Cendekia Publishing, 2023)
This paper analyzes the constraints on supply chain processes within the poultry industry in West Java, Indonesia after COVID-19 pandemic. During the upstream process, poultry feed costs fluctuates greatly and lacks of storage which causing feed supply constraint, the mortality rate of chickens often surpasses 5% due to several factors including stocking density. Another identified problem adversely affecting the upstream process is the inability of small-scale farmers to procure their own Grand Parent Stock (GPS) since they remain dependent upon corporations to supply it, leading to inefficiency and increased production costs. Meanwhile, in downstream processes, the lack of a cold supply chain system and adequate storage capacity presents other challenges with regard to product durability. Consumer awareness regarding the relationship between food safety and health, and shifting in consumer preferences, especially during COVID-19 pandemic is also considered as a constraint in West Java poultry supply chain. To cope with those problems, several solutions such as technology and policy were offered to improve and solve problems in the supply chain process. Technology can be a powerful tool in addressing challenges in the poultry supply chain by providing efficient, accurate, and scalable solutions. While policy play a crucial role in addressing problems in the poultry supply chain by setting standards, promoting best practices, and providing a framework for action, regulate the behavior of the actors, promote transparency and hold actors accountable for their actions. A causal loop diagram is also made to assess the relationship between technology and policy in poultry supply chain process